Optimizing Civil Servants’ Performance Through Digital Governance: A Study on the APD Division of the PMD Office in Sekadau Regency - Agustina Dwi Hendrawati (Pencerah, 2025)
This study examines how digital governance optimizes the performance of civil servants in the APD Division of the Community and Village Empowerment Office (PMD) in Sekadau Regency. The research aims to analyze civil servants’ performance in terms of productivity, effectiveness, efficiency, and service quality within the context of increasing digitalization in public administration. A descriptive qualitative approach was employed, with data collected through observations, in-depth interviews, and documentation involving officers and operational staff. The findings indicate that despite limited human resources—only five civil servants serving 95 villages—the APD Division demonstrates high productivity and strong teamwork, enabling programs and activities to be completed according to planned targets. Performance effectiveness is supported by regular capacity-building programs, adequate work facilities, clear operational guidelines, and the utilization of digital applications such as SISKEUDES and Village Information Systems, which enhance administrative speed and transparency. From an efficiency perspective, digital tools contribute to optimal use of human and financial resources by reducing operational costs without compromising service quality. Public satisfaction with village administrative services reaches approximately 80–85 percent, indicating a high level of service quality. However, challenges remain, including uneven digital infrastructure, limited access to information, and insufficient direct assistance in certain villages. The study concludes that digital governance plays a crucial role in improving civil servants’ performance, but its sustainability requires strengthening infrastructure, increasing personnel, and expanding continuous mentoring to ensure inclusive and effective public service delivery.